A Novel Rehabilitation Program Using Neuromuscular Electrical Stimulation (NMES) and Taping for Shoulder Pain in Swimmers: A Protocol and Case Example - Noah Smith; Rachel Hotze; Angela R Tate (North American Sports Medicine Institute, 2021)
In-pool return to swim protocols have been described for swimmers returning from being deactivated from swimming due to a shoulder injury who have full shoulder strength. Many swimmers actively participate in swim practice and competition with shoulder pain and experience deficits in performance. There are multiple reported risk factors associated with shoulder pain among swimmers, including training errors and physical impairments. These include pool and dry-land training errors, weakness in the scapular stabilizers and rotator cuff, and muscle tightness. A need exists for dry-land rehabilitation programs for impairments common to swimmers that can be performed in a traditional outpatient physical therapy setting. The purpose of this clinical commentary is to present a protocol using neuromuscular electrical stimulation (NMES), taping, strengthening, and stretching to address impairments that are common among swimmers while allowing continued active participation in practice and competition. # Level of Evidence Level 5